Internal inflammatory root resorption in permanent teeth (Эндодонтия Today)
Internal inflammatory root resorption is a rare find in everyday dental practice. Also, it is known to be an accident discovery. Analysis of publications of domestic and foreign periodicals and of biochemistry, histology, microbiology textbooks has allowed to generalize and systematize data on the prevalence in the population, causes, clinical manifestations, diagnosis and differential diagnosis of this disease, as well as reveal the underlying mechanism of its development and histological features.